Report on the geological, geomorphological and geodetic field party in the Sør Rondane Mountains, 1986 (JARE-27) - Kiichi Moriwaki; Hideyasu Kojima; Hideo Ishizuka; Norikazu Matsuoka; Takeji Kometani; Shigeo Shiga; Tomoya Morita; Shigeo Kuriki (National Institute of Polar Research, 1986)
The 27th Japanese Antarctic Research Expedition (JARE-27) carried out the geological, geomorphological and geodetic field work in the central part of the Sør Rondane Mountains for 33 days from January 5 to February 6,1986. The field work was conducted by two parties with four persons each in order to investigate the vast area. They carried out expected investigations on spite of meeting with many crevasses. They used four snow vehicles and six snowmobiles. The snowmobiles were very useful to the field work in the area. This report gives detailed of operation including logistics, a summary of the field work, and information on the weather and the surface condition of snow and ice observed in this period.